DEMOTIVATION IN MANDARIN AS A FOREIGN LANGUAGE AMONG MALAYSIAN TERTIARY STUDENTS - Rokiah, Paee; Lam, Kai Chee; Kuan, Wee Ling; Najwa Hanani, Kopli (Universiti Sultan Zainal Abidin, 2024)
Background and Purpose: Demotivation has been acknowledged as a significant factor in the decrease of student enrolment and the increase in student attrition rates within the domain of Mandarin as a foreign language (MFL) learning. This study seeks to identify the causes of demotivation among learners of MFL at a public tertiary institution in Malaysia.